Zaragoza en la Exposición de París de 1878 a partir de fuentes de archivo y fotografía - Garris Fernández, Alex (MDCCC 1800, 2017)
Since their appearance in the 19th century, universal exhibitions have been closely related to the artistic collections of numerous nations, and they have been a fundamental source for art historians as a historical event in which the most outstanding novelties of each period can be observed. However, the study and more detailed knowledge of the attractive pavilions, or the awardwinning artistic works displayed in these events has diverted the attention from many other artistic projects. The contribution of the Provincial Commission of Monuments of Zaragoza to the 1878 Universal Exhibition not only enabled awareness to be raised about the historical-artistic riches of our province, but also helped spread knowledge about the Aragonese heritage outside our borders through the assembly of a comprehensive catalogue, and a splendid photo album of Aragonese artistic works, which were sent to Paris.